Daniel Miller, 2008, The Comfort of Things, Cambridge, UK & Maiden, MA, USA, Polity Press, 302 σελ. - Καυτανζόγλου, Ρωξάνη (The Greek Review of Social Research, 2014)
Δε διατίθεται περίληψη / no abstract available